2019
DOI: 10.1108/lht-11-2017-0254
|View full text |Cite
|
Sign up to set email alerts
|

An IoT-based risk warning system for smart libraries

Abstract: Purpose When integrating smart elements offered by emergent technologies, libraries are facing the challenges of technological renovation and maintaining their operation using emerging technology. Given the importance of smart library, new technologies are needed in building new libraries or renovation of existing libraries. The purpose of this paper is to propose a risk warning system for library construction or renovation in the aspect of risk management. Design/methodology/approach The proposed Internet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
(88 reference statements)
0
7
0
2
Order By: Relevance
“…The basic set of technologies that is needed for the IoT to function effectively refer to RFID, wireless communication devices, sensors, cloud computing, and advanced Internet Protocol (IP) (Chen 2019). In addition, Xie, Liu, Zhu, Chong, Shi, and Chen (2019) suggest that other technologies should be incorporated as part of the IoT to expand its functionality and relevance. These may include near-field communication (NFC), low-rated wireless personal area networks, Bluetooth, wireless fidelity (Wi-Fi), worldwide interpretability for microwave access (WiMAX), mobile communications, and wireless sensor networks (WSNs).…”
Section: Internet Of Things Architecture Within the Context Of Academ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The basic set of technologies that is needed for the IoT to function effectively refer to RFID, wireless communication devices, sensors, cloud computing, and advanced Internet Protocol (IP) (Chen 2019). In addition, Xie, Liu, Zhu, Chong, Shi, and Chen (2019) suggest that other technologies should be incorporated as part of the IoT to expand its functionality and relevance. These may include near-field communication (NFC), low-rated wireless personal area networks, Bluetooth, wireless fidelity (Wi-Fi), worldwide interpretability for microwave access (WiMAX), mobile communications, and wireless sensor networks (WSNs).…”
Section: Internet Of Things Architecture Within the Context Of Academ...mentioning
confidence: 99%
“…Gul and Bano (2019) state that for academic libraries to become smart, technologies related to electronic resource management, digital asset management, and institutional repositories should also form part of the technologies to be linked to the IoT. Cao et al (2018), Gul and Bano (2019), and Xie et al (2019) propose that IoT technologies used within a smart library context be divided into three layers to ensure that all technology is in place to convert a hybrid or digital academic library to a smart academic library through the application of the IoT. These three layers are the perception layer, the device and network/computing layer, and the access/discovery layer.…”
Section: Internet Of Things Architecture Within the Context Of Academ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Caribbean librarians acquire book information data by using RFID handheld reader for scanning RFID tags of books, while users can opportunely and without difficulty find their desired books through intelligent navigation retrieval terminals. Xie et al (2019) found that by using "RFID tags on books, the system can easily track material flow and visualize logistics processes" ( 22). This ultimately improves the efficiency of material flow and reduces logistics costs in libraries.…”
Section: Backbone For Smart Libraries In the Caribbeanmentioning
confidence: 99%
“…10 Mindebben kiemelt szerepet tölt be a könyvtárépület intelligenciája. 11 A tárgyak internete segítségével a könyvtáraknak lehetőségük van IoT alapú biztonsági rendszer 12 és IoT alapú evakuációs protokoll kidolgozására is. 13 A szolgáltatásokat tekintve az iBeacon alapjaira épülő Bluubeam jeladókat érdemes megemlítenem.…”
Section: Az Okoskönyvtár (Szakirodalmi Kitekintés)unclassified